Difference between revisions of "1989 AIME Problems/Problem 10"

(Solution 8)
 
(10 intermediate revisions by 6 users not shown)
Line 6: Line 6:
 
== Solution ==
 
== Solution ==
 
=== Solution 1 ===
 
=== Solution 1 ===
We can draw the [[altitude]] <math>h</math> to <math>c</math>, to get two [[right triangle]]s. <math>\cot{\alpha}+\cot{\beta}=\frac{c}{h}</math>, from the definition of the [[cotangent]]. From the definition of area, <math>h=\frac{2A}{c}</math>, so <math>\cot{\alpha}+\cot{\beta}=\frac{c^2}{2A}</math>.
+
We draw the [[altitude]] <math>h</math> to <math>c</math>, to get two [[right triangle]]s.
 +
<center><asy>
 +
size(170);
 +
pair A = (0,0), B = (3, 0), C = (1, 4);
 +
pair P = .5*(C + reflect(A,B)*C);
 +
draw(A--B--C--cycle);
 +
draw(C--P, dotted);
 +
draw(rightanglemark(C,P, B, 4));
 +
label("$A$", A, S);
 +
label("$B$", B, S);
 +
label("$C$", C, N);
 +
label("$a$", (B+C)/2, NE);
 +
label("$b$", (A+C)/2, NW);
 +
label("$c$", (A+B)/2, S);
 +
label("$h$", (C+P)/2, E);</asy></center>
  
Now we evaluate the numerator:
+
Then <math>\cot{\alpha}+\cot{\beta}=\frac{c}{h}</math>, from the definition of the [[cotangent]].
 +
 
 +
Let <math>K</math> be the area of <math>\triangle ABC.</math> Then <math>h=\frac{2K}{c}</math>, so <math>\cot{\alpha}+\cot{\beta}=\frac{c^2}{2K}</math>.
 +
 
 +
By identical logic, we can find similar expressions for the sums of the other two cotangents:
 +
<cmath> \begin{align*}
 +
\cot \alpha + \cot \beta &= \frac{c^2}{2K} \\
 +
\cot \beta + \cot \gamma &= \frac{a^2}{2K} \\
 +
\cot \gamma + \cot \alpha &= \frac{b^2}{2K}. \end{align*} </cmath>
 +
Adding the last two equations, subtracting the first, and dividing by 2, we get
 +
<cmath> \cot \gamma = \frac{a^2 + b^2 - c^2}{4K}.</cmath>
 +
Therefore
 +
<cmath> \begin{align*}
 +
\frac{\cot \gamma}{\cot \alpha + \cot \beta} &= \frac{(a^2 + b^2 - c^2)/(4K)}{c^2/(2K)} \\
 +
&= \frac{a^2 + b^2 - c^2}{2c^2} \\
 +
&= \frac{1989 c^2 - c^2}{2c^2} \\
 +
&= \frac{1988}{2} = \boxed{994}. \end{align*} </cmath>
 +
 
 +
=== Solution 2 ===
 +
 
 +
By the [[law of cosines]],
 +
<cmath> \cos \gamma = \frac{a^2 + b^2 - c^2}{2ab}. </cmath> So, by the extended [[law of sines]],
 +
<cmath> \cot \gamma = \frac{\cos \gamma}{\sin \gamma} = \frac{a^2 + b^2 - c^2}{2ab} \cdot \frac{2R}{c} = \frac{R}{abc} (a^2 + b^2 - c^2). </cmath>
 +
Identical logic works for the other two angles in the triangle.  So, the cotangent of any angle in the triangle is directly proportional to the sum of the squares of the two adjacent sides, minus the square of the opposite side.  Therefore
 +
<cmath> \frac{\cot \gamma}{\cot \alpha + \cot \beta} = \frac{a^2 + b^2 - c^2}{(-a^2 + b^2 + c^2) + (a^2 - b^2 + c^2)} = \frac{a^2 + b^2 - c^2}{2c^2}. </cmath>
 +
We can then finish as in solution 1.
 +
 
 +
=== Solution 3 ===
 +
 
 +
We start as in solution 1, though we'll write <math>A</math> instead of <math>K</math> for the area.  Now we evaluate the numerator:
  
 
<cmath>\cot{\gamma}=\frac{\cos{\gamma}}{\sin{\gamma}}</cmath>
 
<cmath>\cot{\gamma}=\frac{\cos{\gamma}}{\sin{\gamma}}</cmath>
Line 20: Line 63:
 
Then <math>\frac{\cot \gamma}{\cot \alpha+\cot \beta}=\frac{\frac{1988c^2}{4A}}{\frac{c^2}{2A}}=\frac{1988}{2}=\boxed{994}</math>.
 
Then <math>\frac{\cot \gamma}{\cot \alpha+\cot \beta}=\frac{\frac{1988c^2}{4A}}{\frac{c^2}{2A}}=\frac{1988}{2}=\boxed{994}</math>.
  
=== Solution 2 ===
+
=== Solution 4 ===
 
<cmath>\begin{align*}
 
<cmath>\begin{align*}
 
\cot{\alpha} + \cot{\beta} &= \frac {\cos{\alpha}}{\sin{\alpha}} + \frac {\cos{\beta}}{\sin{\beta}} = \frac {\sin{\alpha}\cos{\beta} + \cos{\alpha}\sin{\beta}}{\sin{\alpha}\sin{\beta}}\\ &= \frac {\sin{(\alpha + \beta)}}{\sin{\alpha}\sin{\beta}} = \frac {\sin{\gamma}}{\sin{\alpha}\sin{\beta}}
 
\cot{\alpha} + \cot{\beta} &= \frac {\cos{\alpha}}{\sin{\alpha}} + \frac {\cos{\beta}}{\sin{\beta}} = \frac {\sin{\alpha}\cos{\beta} + \cos{\alpha}\sin{\beta}}{\sin{\alpha}\sin{\beta}}\\ &= \frac {\sin{(\alpha + \beta)}}{\sin{\alpha}\sin{\beta}} = \frac {\sin{\gamma}}{\sin{\alpha}\sin{\beta}}
Line 34: Line 77:
  
  
=== Solution 3===
+
=== Solution 5===
  
Use Law of cosines to give us <math>c^2=a^2+b^2-2ab\cos(\gamma)</math> or therefore <math>\cos(\gamma)=\frac{994c^2}{ab}</math>.  Next, we are going to put all the sin's in term of <math>\sin(a)</math>.  We get <math>\sin(\gamma)=\frac{c\sin(a)}{a}</math>.  Therefore, we get <math>\cot(\gamma)=\frac{994c}{b\sina}</math>.
+
Use Law of cosines to give us <math>c^2=a^2+b^2-2ab\cos(\gamma)</math> or therefore <math>\cos(\gamma)=\frac{994c^2}{ab}</math>.  Next, we are going to put all the sin's in term of <math>\sin(a)</math>.  We get <math>\sin(\gamma)=\frac{c\sin(a)}{a}</math>.  Therefore, we get <math>\cot(\gamma)=\frac{994c}{b\sin a}</math>.
  
 
Next, use Law of Cosines to give us <math>b^2=a^2+c^2-2ac\cos(\beta)</math>.  Therefore, <math>\cos(\beta)=\frac{a^2-994c^2}{ac}</math>.  Also, <math>\sin(\beta)=\frac{b\sin(a)}{a}</math>.  Hence, <math>\cot(\beta)=\frac{a^2-994c^2}{bc\sin(a)}</math>.   
 
Next, use Law of Cosines to give us <math>b^2=a^2+c^2-2ac\cos(\beta)</math>.  Therefore, <math>\cos(\beta)=\frac{a^2-994c^2}{ac}</math>.  Also, <math>\sin(\beta)=\frac{b\sin(a)}{a}</math>.  Hence, <math>\cot(\beta)=\frac{a^2-994c^2}{bc\sin(a)}</math>.   
Line 42: Line 85:
 
Lastly, <math>\cos(\alpha)=\frac{b^2-994c^2}{bc}</math>. Therefore, we get <math>\cot(\alpha)=\frac{b^2-994c^2}{bc\sin(a)}</math>.
 
Lastly, <math>\cos(\alpha)=\frac{b^2-994c^2}{bc}</math>. Therefore, we get <math>\cot(\alpha)=\frac{b^2-994c^2}{bc\sin(a)}</math>.
  
Now, <math>\frac{\cot(\gamma)}{\cot(\beta)+\cot(\alpha)}=\frac{\frac{994c}{b\sina}}{\frac{a^2-994c^2+b^2-994c^2}{bc\sin(a)}}</math>.  After using <math>a^2+b^2=1989c^2</math>, we get <math>\frac{994c*bc\sina}{c^2b\sina}=\boxed{994}</math>.
+
Now, <math>\frac{\cot(\gamma)}{\cot(\beta)+\cot(\alpha)}=\frac{\frac{994c}{b\sin a}}{\frac{a^2-994c^2+b^2-994c^2}{bc\sin(a)}}</math>.  After using <math>a^2+b^2=1989c^2</math>, we get <math>\frac{994c*bc\sin a}{c^2b\sin a}=\boxed{994}</math>.
 +
 
 +
 
 +
=== Solution 6===
 +
 
 +
 
 +
Let <math>\gamma</math> be <math>(180-\alpha-\beta)</math>
 +
 
 +
<math>\frac{\cot \gamma}{\cot \alpha+\cot \beta} = \frac{\frac{-\tan \alpha \tan \beta}{\tan(\alpha+\beta)}}{\tan \alpha + \tan \beta} = \frac{(\tan \alpha \tan \beta)^2-\tan \alpha \tan \beta}{\tan^2 \alpha + 2\tan \alpha \tan \beta +\tan^2 \beta}</math>
 +
 
 +
WLOG, assume that <math>a</math> and <math>c</math> are legs of right triangle <math>abc</math> with <math>\beta = 90^o</math> and <math>c=1</math>
 +
 
 +
By the Pythagorean theorem, we have <math>b^2=a^2+1</math>, and the given <math>a^2+b^2=1989</math>. Solving the equations gives us <math>a=\sqrt{994}</math> and <math>b=\sqrt{995}</math>. We see that <math>\tan \beta = \infty</math>, and <math>\tan \alpha = \sqrt{994}</math>.
 +
 
 +
Our derived equation equals <math>\tan^2 \alpha</math> as <math>\tan \beta</math> approaches infinity.
 +
Evaluating <math>\tan^2 \alpha</math>, we get <math>\boxed{994}</math>.
 +
 
 +
 
 +
=== Solution 7===
 +
 
 +
As in Solution 1, drop an altitude <math>h</math> to <math>c</math>. Let <math>h</math> meet <math>c</math> at <math>P</math>, and let <math>AP = x, BP = y</math>.
 +
 
 +
<center><asy>
 +
size(170);
 +
pair A = (0,0), B = (3,0), C = (1,4);
 +
pair P = .5*(C + reflect(A,B)*C);
 +
draw(A--B--C--cycle);
 +
draw(C--P, dotted);
 +
draw(rightanglemark(C,P, B , 4));
 +
label("$A$", A, S);
 +
label("$B$", B, S);
 +
label("$C$", C, N);
 +
label("$P$", P, S);
 +
label("$x$", (A+P)/2, S);
 +
label("$y$", (B+P)/2, S);
 +
label("$a$", (B+C)/2, NE);
 +
label("$b$", (A+C)/2, NW);
 +
label("$c$", (A+B)/2, S);
 +
label("$h$", (C+P)/2, E);</asy></center>
 +
 
 +
Then, <math>\cot{\alpha} = \frac{1}{\tan{\alpha}} = \frac{x}{h}</math>, <math>\cot{\beta} = \frac{1}{\tan{\beta}} = \frac{y}{h}</math>. We can calculate <math>\cot{\gamma}</math> using the [[tangent addition formula]], after noticing that <math>\cot{\gamma} = \frac{1}{\tan{\gamma}}</math>. So, we find that
 +
\begin{align*}
 +
\cot{\gamma} &= \frac{1}{\tan{\gamma}} \\
 +
&= \frac{1}{\frac{\frac{x}{h} + \frac{y}{h}}{1 - \frac{xy}{h^2}}} \\
 +
&= \frac{1}{\frac{(x+y)h}{h^2 - xy}} \\
 +
&= \frac{h^2 - xy}{(x+y)h}.
 +
\end{align*}
 +
 
 +
So now we can simplify our original expression:
 +
\begin{align*}
 +
\frac{\cot{\gamma}}{\cot{\alpha} + \cot{\beta}} &= \frac{\frac{h^2 - xy}{(x+y)h}}{\frac{x + y}{h}} \\
 +
&= \frac{h^2 - xy}{(x+y)^2}.
 +
\end{align*}
 +
 
 +
But notice that <math>x+y = c</math>, so this becomes <cmath>\frac{h^2 - xy}{c^2}.</cmath>
 +
Now note that we can use the [[Pythagorean theorem]] to calculate <math>h^2</math>, we get that <cmath>h^2 = \frac{a^2 - y^2 + b^2 - x^2}{2}.</cmath>
 +
So our expression simplifies to <cmath>\frac{1989c^2 - (x+y)^2}{2c^2}</cmath>
 +
since <math>a^2 + b^2 = 1989c^2</math> from the problem and that there is another <math>-\frac{2xy}{2}</math> after the <math>h^2</math> in our expression. Again note that <math>x+y = c</math>, so it again simplifies to <math>\frac{1988c^2}{2c^2}</math>, or <math>\boxed{994}</math>.
 +
 
 +
~[[User: Yiyj1|Yiyj1]]
 +
 
 +
 
 +
 
 +
=== Solution 8 (Quick and Easy) ===
 +
 
 +
Since no additional information is given, we can assume that triangle ABC is right with the right angle at B.
 +
We can use the [[Pythagorean theorem]] to say <cmath>c^2+a^2=b^2</cmath>
 +
We can now solve for <math>a</math> in terms of <math>c</math>
 +
 
 +
<cmath>c^2+a^2=1989c^2-a^2</cmath>
 +
<cmath>a^2=994c^2</cmath>
 +
<cmath>a=\sqrt{994}c</cmath>
 +
 
 +
Using the definition of cotangent
 +
 
 +
<cmath>cot(A)=\frac{c}{a}=\frac{1}{\sqrt{994}}</cmath>
 +
<cmath>cot(B)=cot(90)=0</cmath>
 +
<cmath>cot(C)=\frac{a}{c}=\sqrt{994}</cmath>
 +
Plugging into our desired expression, we get <math>\boxed{994}</math>
 +
 
 +
~[[User: ms0001|ms0001]]
  
 
== See also ==
 
== See also ==

Latest revision as of 21:41, 20 January 2024

Problem

Let $a$, $b$, $c$ be the three sides of a triangle, and let $\alpha$, $\beta$, $\gamma$, be the angles opposite them. If $a^2+b^2=1989c^2$, find

$\frac{\cot \gamma}{\cot \alpha+\cot \beta}$

Solution

Solution 1

We draw the altitude $h$ to $c$, to get two right triangles.

[asy] size(170); pair A = (0,0), B = (3, 0), C = (1, 4); pair P = .5*(C + reflect(A,B)*C); draw(A--B--C--cycle); draw(C--P, dotted); draw(rightanglemark(C,P, B, 4)); label("$A$", A, S); label("$B$", B, S); label("$C$", C, N); label("$a$", (B+C)/2, NE); label("$b$", (A+C)/2, NW); label("$c$", (A+B)/2, S); label("$h$", (C+P)/2, E);[/asy]

Then $\cot{\alpha}+\cot{\beta}=\frac{c}{h}$, from the definition of the cotangent.

Let $K$ be the area of $\triangle ABC.$ Then $h=\frac{2K}{c}$, so $\cot{\alpha}+\cot{\beta}=\frac{c^2}{2K}$.

By identical logic, we can find similar expressions for the sums of the other two cotangents: \begin{align*} \cot \alpha + \cot \beta &= \frac{c^2}{2K} \\ \cot \beta + \cot \gamma &= \frac{a^2}{2K} \\ \cot \gamma + \cot \alpha &= \frac{b^2}{2K}. \end{align*} Adding the last two equations, subtracting the first, and dividing by 2, we get \[\cot \gamma = \frac{a^2 + b^2 - c^2}{4K}.\] Therefore \begin{align*} \frac{\cot \gamma}{\cot \alpha + \cot \beta} &= \frac{(a^2 + b^2 - c^2)/(4K)}{c^2/(2K)} \\ &= \frac{a^2 + b^2 - c^2}{2c^2} \\ &= \frac{1989 c^2 - c^2}{2c^2} \\ &= \frac{1988}{2} = \boxed{994}. \end{align*}

Solution 2

By the law of cosines, \[\cos \gamma = \frac{a^2 + b^2 - c^2}{2ab}.\] So, by the extended law of sines, \[\cot \gamma = \frac{\cos \gamma}{\sin \gamma} = \frac{a^2 + b^2 - c^2}{2ab} \cdot \frac{2R}{c} = \frac{R}{abc} (a^2 + b^2 - c^2).\] Identical logic works for the other two angles in the triangle. So, the cotangent of any angle in the triangle is directly proportional to the sum of the squares of the two adjacent sides, minus the square of the opposite side. Therefore \[\frac{\cot \gamma}{\cot \alpha + \cot \beta} = \frac{a^2 + b^2 - c^2}{(-a^2 + b^2 + c^2) + (a^2 - b^2 + c^2)} = \frac{a^2 + b^2 - c^2}{2c^2}.\] We can then finish as in solution 1.

Solution 3

We start as in solution 1, though we'll write $A$ instead of $K$ for the area. Now we evaluate the numerator:

\[\cot{\gamma}=\frac{\cos{\gamma}}{\sin{\gamma}}\]

From the Law of Cosines and the sine area formula,

\begin{align*}\cos{\gamma}&=\frac{1988c^2}{2ab}\\ \sin{\gamma}&= \frac{2A}{ab}\\ \cot{\gamma}&= \frac{\cos \gamma}{\sin \gamma} = \frac{1988c^2}{4A} \end{align*}

Then $\frac{\cot \gamma}{\cot \alpha+\cot \beta}=\frac{\frac{1988c^2}{4A}}{\frac{c^2}{2A}}=\frac{1988}{2}=\boxed{994}$.

Solution 4

\begin{align*} \cot{\alpha} + \cot{\beta} &= \frac {\cos{\alpha}}{\sin{\alpha}} + \frac {\cos{\beta}}{\sin{\beta}} = \frac {\sin{\alpha}\cos{\beta} + \cos{\alpha}\sin{\beta}}{\sin{\alpha}\sin{\beta}}\\ &= \frac {\sin{(\alpha + \beta)}}{\sin{\alpha}\sin{\beta}} = \frac {\sin{\gamma}}{\sin{\alpha}\sin{\beta}} \end{align*}

By the Law of Cosines,

\[a^2 + b^2 - 2ab\cos{\gamma} = c^2 = 1989c^2 - 2ab\cos{\gamma} \implies ab\cos{\gamma} = 994c^2\]

Now

\begin{align*}\frac {\cot{\gamma}}{\cot{\alpha} + \cot{\beta}} &= \frac {\cot{\gamma}\sin{\alpha}\sin{\beta}}{\sin{\gamma}} = \frac {\cos{\gamma}\sin{\alpha}\sin{\beta}}{\sin^2{\gamma}} = \frac {ab}{c^2}\cos{\gamma} = \frac {ab}{c^2} \cdot \frac {994c^2}{ab}\\ &= \boxed{994}\end{align*}


Solution 5

Use Law of cosines to give us $c^2=a^2+b^2-2ab\cos(\gamma)$ or therefore $\cos(\gamma)=\frac{994c^2}{ab}$. Next, we are going to put all the sin's in term of $\sin(a)$. We get $\sin(\gamma)=\frac{c\sin(a)}{a}$. Therefore, we get $\cot(\gamma)=\frac{994c}{b\sin a}$.

Next, use Law of Cosines to give us $b^2=a^2+c^2-2ac\cos(\beta)$. Therefore, $\cos(\beta)=\frac{a^2-994c^2}{ac}$. Also, $\sin(\beta)=\frac{b\sin(a)}{a}$. Hence, $\cot(\beta)=\frac{a^2-994c^2}{bc\sin(a)}$.

Lastly, $\cos(\alpha)=\frac{b^2-994c^2}{bc}$. Therefore, we get $\cot(\alpha)=\frac{b^2-994c^2}{bc\sin(a)}$.

Now, $\frac{\cot(\gamma)}{\cot(\beta)+\cot(\alpha)}=\frac{\frac{994c}{b\sin a}}{\frac{a^2-994c^2+b^2-994c^2}{bc\sin(a)}}$. After using $a^2+b^2=1989c^2$, we get $\frac{994c*bc\sin a}{c^2b\sin a}=\boxed{994}$.


Solution 6

Let $\gamma$ be $(180-\alpha-\beta)$

$\frac{\cot \gamma}{\cot \alpha+\cot \beta} = \frac{\frac{-\tan \alpha \tan \beta}{\tan(\alpha+\beta)}}{\tan \alpha + \tan \beta} = \frac{(\tan \alpha \tan \beta)^2-\tan \alpha \tan \beta}{\tan^2 \alpha + 2\tan \alpha \tan \beta +\tan^2 \beta}$

WLOG, assume that $a$ and $c$ are legs of right triangle $abc$ with $\beta = 90^o$ and $c=1$

By the Pythagorean theorem, we have $b^2=a^2+1$, and the given $a^2+b^2=1989$. Solving the equations gives us $a=\sqrt{994}$ and $b=\sqrt{995}$. We see that $\tan \beta = \infty$, and $\tan \alpha = \sqrt{994}$.

Our derived equation equals $\tan^2 \alpha$ as $\tan \beta$ approaches infinity. Evaluating $\tan^2 \alpha$, we get $\boxed{994}$.


Solution 7

As in Solution 1, drop an altitude $h$ to $c$. Let $h$ meet $c$ at $P$, and let $AP = x, BP = y$.

[asy] size(170); pair A = (0,0), B = (3,0), C = (1,4); pair P = .5*(C + reflect(A,B)*C); draw(A--B--C--cycle); draw(C--P, dotted); draw(rightanglemark(C,P, B , 4)); label("$A$", A, S); label("$B$", B, S); label("$C$", C, N); label("$P$", P, S); label("$x$", (A+P)/2, S); label("$y$", (B+P)/2, S); label("$a$", (B+C)/2, NE); label("$b$", (A+C)/2, NW); label("$c$", (A+B)/2, S); label("$h$", (C+P)/2, E);[/asy]

Then, $\cot{\alpha} = \frac{1}{\tan{\alpha}} = \frac{x}{h}$, $\cot{\beta} = \frac{1}{\tan{\beta}} = \frac{y}{h}$. We can calculate $\cot{\gamma}$ using the tangent addition formula, after noticing that $\cot{\gamma} = \frac{1}{\tan{\gamma}}$. So, we find that \begin{align*} \cot{\gamma} &= \frac{1}{\tan{\gamma}} \\ &= \frac{1}{\frac{\frac{x}{h} + \frac{y}{h}}{1 - \frac{xy}{h^2}}} \\ &= \frac{1}{\frac{(x+y)h}{h^2 - xy}} \\ &= \frac{h^2 - xy}{(x+y)h}. \end{align*}

So now we can simplify our original expression: \begin{align*} \frac{\cot{\gamma}}{\cot{\alpha} + \cot{\beta}} &= \frac{\frac{h^2 - xy}{(x+y)h}}{\frac{x + y}{h}} \\ &= \frac{h^2 - xy}{(x+y)^2}. \end{align*}

But notice that $x+y = c$, so this becomes \[\frac{h^2 - xy}{c^2}.\] Now note that we can use the Pythagorean theorem to calculate $h^2$, we get that \[h^2 = \frac{a^2 - y^2 + b^2 - x^2}{2}.\] So our expression simplifies to \[\frac{1989c^2 - (x+y)^2}{2c^2}\] since $a^2 + b^2 = 1989c^2$ from the problem and that there is another $-\frac{2xy}{2}$ after the $h^2$ in our expression. Again note that $x+y = c$, so it again simplifies to $\frac{1988c^2}{2c^2}$, or $\boxed{994}$.

~Yiyj1


Solution 8 (Quick and Easy)

Since no additional information is given, we can assume that triangle ABC is right with the right angle at B. We can use the Pythagorean theorem to say \[c^2+a^2=b^2\] We can now solve for $a$ in terms of $c$

\[c^2+a^2=1989c^2-a^2\] \[a^2=994c^2\] \[a=\sqrt{994}c\]

Using the definition of cotangent

\[cot(A)=\frac{c}{a}=\frac{1}{\sqrt{994}}\] \[cot(B)=cot(90)=0\] \[cot(C)=\frac{a}{c}=\sqrt{994}\] Plugging into our desired expression, we get $\boxed{994}$

~ms0001

See also

1989 AIME (ProblemsAnswer KeyResources)
Preceded by
Problem 9
Followed by
Problem 11
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15
All AIME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png